Comparing the effects of group discussion and lecture educational methods on preventive behaviors of high blood pressure in Eslamshahr women - Ramezankhani, Ali; Pooresmaeil, Ameneh; Rakhshandehrou, Sakineh; Khodakarim, Soheila (Researcher Bulletin of Medical Sciences, 2020)
Introduction: Nowadays, high blood pressure is a major risky factor for heart disease, stroke and kidney diseases and education is one of the effective factors that reduces high blood pressure. This study was designed and conducted to compare the effects of group discussion and lecture methods on preventive behaviors of high blood pressure in Eslamshahr school students’ mothers. Materials & Methods: In this experimental study, a two-stage cluster sampling was conducted and 168 students were selected. Then, these students were divided into three groups of 56 members each. In addition, their mothers were invited to participate in the study. Samples into three groups (two case groups and a control group) were divided into three stages and with a questionnaire which consists of demographic information questions and questions related to knowledge, attitude, behavior developed by the researcher, were evaluated. provide educational content, lectures and group discussion methods were to used. Data collected using software SPSS-21 and ANOVA, chi-square test and Kruskal-Wallis test were used. Results: The test showed significant differences between the two methods in the confidence level of 0.95, so that the ratings of knowledge and attitudes and preventive behaviors were higher in grou discussion (p<0.001). These results suggest that education in group discussion in comparison with lecture method is more effective and encouraging. Conclusion: The results showed that the group discussion method is more effective than lecture is. therefore recommended to pay more attention to high blood pressure in mothers, in this educational method, especially in the education of preventive behaviors.